ENRICHING STUDENTS VOCABULARY THROUGH SPELLING BEE GAME - Saiya, Tesalonika Mercy; Oroh, Elisabeth Z.; Sanger, Maikel (SoCul: International Journal of Research in Social Cultural Issues, 2022)
The purpose of this research is to investigate the effectiveness of the Spelling Bee game in enriching students vocabulary This study was carried out at SMK Negeri 2 Tondano in which the subject was the 10th< sup> grade tourism department students which consist of 12 students This research used quantitative research through the pre experimental design with one group pre test and post test design The data of this research were collected by using tests in the form of pre test and post test The result of this research showed that the scores of the students in the post test are higher than the pre test The mean of the post test was 89 21 while the mean of the pre test was 58 49 It means that using the Spelling Bee game in teaching vocabulary is effective in enriching students vocabulary < p>